Dielectric and gamma shielding properties of sodium silicate glassy structure modified with tungsten. Issue 3 (3rd April 2019) - Kılıç, Mehmet; Çağlar, Mustafa; Karabul, Yaşar; Güven Özdemir, Zeynep; İçelli, Orhan
ABSTRACT: In this study, ( x )%Na2 Si3 O7 /(100 −  x )%W glassy structured composites where x  = 100, 25 and 60 were prepared for the investigation of their dielectric and gamma-ray shielding properties for the first time. The surface morphology of the samples was imaged by Scanning Electron Microscope. The room temperature complex impedance and dielectric function analysis of the samples revealed that the Na2 Si3 O7 /40%W composite has a promising potential for the decoupling capacitor and electromagnetic shielding applications. From this point of view, the gamma-ray shielding performance of the samples including pure Na2 Si3 O7 was tested by Ba-133 radioactive point source for transmission of the gamma rays at 81 and 356 keV photon energies. The mass attenuation coefficients ( μ / ρ ) of the composites were measured at these energies by using NaI(Tl) scintillation detector. The experimental half-value layer (HVL), tenth-value layer (TVL) and mean free path ( λ ) were also calculated. The theoretical values of the ( μ / ρ ), HVL, TVL and λ were determined by using Monte Carlo N-Particle simulation code and WinXCom for the comparison. A good agreement between the experimental and theoretical results for the gamma-ray shielding parameters was obtained. While the mass attenuation coefficient increased considerably with an increasing tungsten concentration doping, it decreased with increasing gamma-ray energy. It was observed that the mass attenuation coefficient of Na2 Si3 O7 /40%W composite is higher than that of lead at 81 keV. In addition, HVL, TVL and λ parameters were found to decrease with increasing W doping. Since there is a good agreement between MNCP results and experimental data, the gamma radiation shielding performance of the samples for some low and high energetic gamma-ray sources such as Am-241, I-131, Cs-137 and Co-60. Ultimately, Na2 Si3 O7 /40%W composite can be suggested as a new alternative non-toxic radiation shielding material for low energetic gamma rays.